THE COMPLEX OF STANDS FOR TESTING THE AIR CUSHION CHASSIS OF AIRCRAFT AND VEHICLES - V. A. Brusov; A. V. Katunin; Y. Y. Merzlikin; D. A. Chizhov (Научный вестник МГТУ ГА, 2016)
This article deals with a set of stands made in NIMK TSAGI for testing and creating the air cushion chassis for the aircraft and vehicles. It allows to fully embrace the process of developing and constructing the air cushion chassis for aircraft and solve problems relating to peculiarities of such aircraft on the takeoff, landing and movement in the elementary prepared and unprepared soil runways, flat terrain and water areas. The complex includes: the experimental installation to study aeroelasticity phenomena of the chassis in the extending and retracting process with simulation of aircraft and ekranoplane takeoff and landing modes in the air flow, including the wind tunnels; the experimental stand with vertical screen for testing of ekranoplane models in T-5 wind tunnel of NIMC TsAGI, permitting to simultaneously vary the model’s position relatively to the screen, roll, pitch (angle of attack), and banking; mobile experimental stand with contact crawler gear, for experimental determination and comparative evaluation of the chassis with different patterns of formation and air cushion fences for all-year-round testing in natural conditions at elementary-prepared and unprepared sites and water areas. Based on mathematical simulation of flow past in the wind tunnel the possibility of use booth stand with vertical screen and experimental installation to study aeroelasticity phenomena of the chassis for experimental studies, respectively, by definition of the aerodynamic characteristics of forces and moments of the air cushion aircraft and ekranoplanes models and the research of phenomena of aeroelasticity of flexible fencing is substantiated.